Pengaruh Digital Marketing dan Kualitas Pelayanan terhadap Keputusan Pembelian Konsumen Coffe Shop pada Kedai Kopi Anaqi Di Kabupaten Subang - Susi Tri Oktaviani Putri; Eman Sulaeman (J-MAS (Jurnal Manajemen dan Sains), 2022)
This study aims to examine and analyze the effect of digital marketing and service quality on coffee shop consumer purchasing decisions. The survey was conducted at the Anaqi Coffee Shop, Subang Regency. This study uses primary data obtained from the results of distributing questionnaires to consumers of the Anaqi Coffee Shop.The method used in this research is quantitative with a descriptive and verification approach. The samples used were 381 samples from 7,901 populations which were taken using non-propabillity sampling method with accidental sampling technique. The analytical technique used in this study is Scale Range Analysis and Path Analysis using the Succesive Interval (MSI) Method and SPSS 26 Software.The results showed that Digital Marketing, Service Quality and Purchase Decisions were in the good category. This means that the Digital Marketing and Service Quality carried out by the Anaqi Coffee Shop is good for consumers so they decide to make a purchase. Partially Digital Marketing has a significant effect on Purchase Decisions, Service Quality has a significant effect on Purchase Decisions. Simultaneously Digital Marketing and Service Quality affect the Purchase Decision.